PATHOGENICITY STUDY OF ESCHERICHIA COLI ISOLATED FROM POULTRY ON BROILER CHICKEN AT 15-DAYS OF AGE - Haryadi Wibowo, Michael; Endang Trihapsari Wahyuni, Agnesia (Jurnal Veteriner; Vol 9 No 2 (2008), 2008)
A study was conducted to determine the pathogenicity of Escherichia coli isolated from chickens. Three isolates, Kalasan (Ec/Kls/4/02), Sleman (Ec/Sl/1/02), and Wonosari (Ec/Wno/2/02) were firstly selected and inoculated into broiler chickens at 15 days of age. Two isolates, Kalasan (Ec/Kls/4/02) and Sleman (Ec/Sl/1/02) which showed clear clinical signs and macroscopic lesions, were cultured in Brain Hearth Infussion (BHI) media for 24 hours at 37oC. Serials ten fold dilution of the purified colonies, starting from 10 1 to 10 10 was prepared and 0,5 ml bacterial sample from each dilution were inoculated intraperitoneally into 5 chickens of 15 day-old. The inoculated chickens were monitored for seven days to observe the clinical signs and microscopic lesions. The infective dose (ID)50 of each isolate was determined by Reed and Muench method. The result showed that the two isolates were pathogenic to 15 day-old broiler chickens with specific lesions of pericarditis, perihepatitis, peritonitis, and airsacculitis. Their infective dose-50 was 2 X 10 2,6 bacterial cells per ml for Kalasan isolate and 2 X 10 1,8 bacterial cells per ml for Sleman isolate. It appeared that Kalasan isolate was more pathogenic than Sleman isolate.
Keywords: Escherichia coli, pathogenic, infection dose